2020
DOI: 10.3126/nmj.v3i2.35117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum of Infertile Couple: a Retrospective Study at Teaching Hospital

Abstract: Introduction: Infertility has been rising steeply as the prime health issue among women around the world these days. This study aims to investigate the causes, hormonal profi le, and clinical spectrum of infertility.Materials and Methods: This is a descriptive cross-sectional study conducted throughout a one year duration in an infertility clinic. The couples meeting the inclusion criteria were included and a pre-formed proforma was used to collect the data regarding history, examination, and investigations.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…Among the women attending the infertility clinic, tubal factors are the most important abnormality because of their complexity in the management. The current study revealed tubal pathology as the commonest as compared to ovarian (35.16% and 32.03% respectively) which is similar to the previous studies 12,13 and contrary to the finding of another study 14 where ovarian pathology was the leading factor for infertility among Nepali women. This higher rate of tubal pathologies are mainly due to reproductive tract infections.…”
Section: Discussionsupporting
confidence: 81%
“…Among the women attending the infertility clinic, tubal factors are the most important abnormality because of their complexity in the management. The current study revealed tubal pathology as the commonest as compared to ovarian (35.16% and 32.03% respectively) which is similar to the previous studies 12,13 and contrary to the finding of another study 14 where ovarian pathology was the leading factor for infertility among Nepali women. This higher rate of tubal pathologies are mainly due to reproductive tract infections.…”
Section: Discussionsupporting
confidence: 81%
“…The most common characteristic in this study was teratozoopermia as with previous studies [14,23]. However, asthenozoospermia [22,24], and oligozoospermia [16] were also found to be the most common semen characteristics in Nepal.…”
Section: Discussionsupporting
confidence: 77%